Graft-versus-host disease complicated with small bowel obstruction in children: A case report - Wang, Yizhong; Liu, Jiangbin; Jiang, Bingxin; Yuan, Chenling; Chen, Licai; Zhang, Ting; Lv, Zhibao (Frontiers in Oncology, 2022)
Graft-versus-host disease (GvHD) is a severe complication following hematopoietic cell transplantation (HCT). The clinical manifestations of GvHD can affect multiple systems. Although gastrointestinal (GI) GvHD is common, GI obstruction complications are rare. Here, we present a case of GI-GvHD after HCT for acute myeloid leukemia (AML) in a young female child from China. The patient suffered from watery diarrhea, which progressed to bloody diarrhea 40 days after HCT. She experienced prolonged and repeated mucous or bloody stool after the withdrawal of cyclosporine and the gradual reduction of methylprednisolone. The plain abdominal radiography and computed tomographic (CT) scan showed apparent bowel wall thickening and intestinal stenosis 10 months after HCT. Finally, the patient underwent surgery to remove the small intestinal stenosis at the age of 26 months. The patient recovered with the help of appropriate medical therapies and nutritional support during hospitalization. She remained stable, and there was no recurrence of GI symptoms 16 months after the surgery. In summary, surgery may be an optimal treatment for GvHD patients with persistent bowel obstruction and failure of appropriate immunosuppressive therapies.